Art and Indifference. Marcel Proust’s In Search of Lost Time in the Light of the Challenges of Orpheus—the Perspective of Making Indifference Present - Orlik, Piotr (Sensus Historiae, 2023)
The following article utilizes the concept of making indifference present as a framework for presented analyses. The associations between indifference and art may be discerned in the ancient myth of Orpheus. Their reconstruction allows us to examine in their light the challenges of indifference contained in the novel In Search of Lost Time by Marcel Proust. The works of the French writer intrigue thinkers that represented various theoretical traditions, such as Roland Barthes, Walter Benjamin, Richard Rorty, Georges Poulet, Paul Ricoeur, Paul de Man, Gilles Deleuze, Maurice Blanchot, and Jean-François Revel. Their conclusions and interpretations were taken up in the analysis of Proust’s In Search of Lost Time from the perspective of making indifference present. Diverse forms of acts of anticipation of indifference are present in the first six volumes of Proust’s novel. Those acts are necessary in order to observe the emergence of post-indifferential sensitivity and post-indifferential wholeness in the final, seventh volume of the novel. Indifference, made present by anticipation (within the first six volumes), induced bracketing of so many seemingly insurmountable differences that a breakthrough was possible, one that Proust attempted to recount within the seventh volume of the novel, which can be considered a transition from anticipation of indifference to retrospection of indifference.